(untitled) (KONFERENSIYA, 2025)
This article explores the often-overlooked linguistic phenomenon of dysphemism, which are derogatory or offensive terms used to describe people, places, or things. While euphemisms soften the impact of words, dysphemism intentionally amplify their negative connotations. This abstract will outline the structure of the article, which includes an introduction to dysphemism, their impact on communication and society, notable examples across different languages, and strategies for addressing and mitigating their use